A Narrative Review Examining the Impact of Clinical Pharmacist Intervention in Rational Antibiotic Use in Pediatric Patients - Mohammad Azeem; Pankaj Arora; Yousif Alosaily; Aifan Saad Alrsheedi (Advanced Concepts in Medicine and Medical Research Vol. 12, 2024)
The drastic changes regarding the growth in demand for pharmacists in healthcare and patient needs have been significant in parallel to the redefinition of the educational and professional responsibilities of pharmacists. Irrational use of antibiotics is one of the major problems for many developing countries and the rapid growth of antibiotic resistance is widely acknowledged. Irrational practice of antibiotics comprises prescription of incorrect dose, duration, route of administration, and regimen frequency and are influenced by certain interrelated factors and drivers. The primary complications of irrational antibiotic use are antibiotic resistance with an increase in poorer health outcomes, increased healthcare costs, more extended hospitalization, and higher mortality, particularly in the pediatric population. WHO identified India as one of the top countries with higher rates of antibiotic resistance globally with proven reports of inappropriate and irrational use of antibiotics resulting in increased incidence and the threat of antimicrobial resistance. The scope of clinical pharmacy delineates the promising use of antibiotics more rationally than ever. Clinical pharmacists are responsible for achieving goals by spreading awareness and educating about optimal drug use to govern pharmaceutical promotions at the hospital, subsequently progressing outcomes. The narrative review aimed to discuss major influencing factors and compilations associated with irrational antibiotic use, concerns in the pediatric population regarding pharmacokinetic/pharmacodynamic characteristics, and the contribution of clinical pharmacist intervention in addressing the global concern of irrational antibiotic use. Clinical pharmacist services can help to determine appropriate antibiotic dosing regimens in pediatric populations concerning physiological and anatomical changes.